2011
DOI: 10.1021/nl103349s
|View full text |Cite
|
Sign up to set email alerts
|

Nanotopographic Control of Neuronal Polarity

Abstract: We employ simple geometrical rules to design a set of nanotopographies able to interfere with focal adhesion establishment during neuronal differentiation. Exploiting nanoimprint lithography techniques on cyclic-olefin-copolymer films, we demonstrate that by varying a single topographical parameter the orientation and maturation of focal adhesions can be finely modulated yielding independent control over the final number and the outgrowth direction of neurites. Taken together, this report provides a novel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
167
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(177 citation statements)
references
References 30 publications
10
167
0
Order By: Relevance
“…Conversely, small neuronal cell models, such as PC12 or SH-SY5Y (cell body diameter approx. 10 mm), followed 500 nm ridges more efficiently than larger features [31,49]. Overall, larger neuronal cells seem to respond better to larger GR periodicity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Conversely, small neuronal cell models, such as PC12 or SH-SY5Y (cell body diameter approx. 10 mm), followed 500 nm ridges more efficiently than larger features [31,49]. Overall, larger neuronal cells seem to respond better to larger GR periodicity.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, in the last few years nanogratings-anisotropic topographies composed of alternating lines of grooves and ridges with submicrometre lateral dimensions-have been intensively investigated and have emerged as one of the most effective systems for inducing neuronal alignment via pure cell mechanotransduction. In previous studies, we showed that the interaction of nerve growth factor (NGF)-differentiating PC12 cells with these substrates promotes bipolarity and alignment to the substrate topography by interfering with FA establishment and maturation [29][30][31]. The ability to direct neurite growth depends on both the dimensions of the underlying patterned substrate and, very importantly, on the neuronal cell type [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In fact, recent in vivo evidence [5][6][7] led to the hypothesis that axially aligned micron-scale topography which incorporates submicronscale features is required for the effective recovery of long (>20 mm) peripheral nerve defects. 8 Topography with micron-scale feature sizes is typically created via standard photolithography on suitable masking layers, whose pattern is subsequently transferred to the substrate typically through an etching process.…”
mentioning
confidence: 99%
“…These observations are consistent with the literature, where the tendency of neurites to elongate along edges 9,11 and channels 1 has been repeatedly demonstrated. Groove or ridge width appears to be the main factor determining the alignment of neurites to topographical features, where 200 nm and 500-1000 nm widths have been shown to be ideal for dorsal root ganglia neurons 4 and differentiating PC12 cells, 3 respectively. Finally, to test microfluidic integration with microtopography, we bonded a bicompartmental neuron culture device described.…”
mentioning
confidence: 99%
“…However, developmental processes such as axon pathfinding, synapse formation, nervous system patterning, neuronal plasticity, and degeneration fail to be explained solely on the basis of soluble factors. There is increasing evidence that physical variables such as the stiffness of a cellular environment influence cell development (7)(8)(9)(10)(11)(12). However, the cells of the brain tissue reside in a soft environment that is rich in polysaccharides (13,14).…”
mentioning
confidence: 99%